Peran Media Sosial dalam Pembentukan Identitas Sosial Anak Muda - Nugraeni, Amelia (LANCAH: Jurnal Inovasi dan Tren, 2024)
The role of social media in forming the social identity of young people has become a significant phenomenon in the digital era. Social media provides a platform for them to convey their values, interests, and preferences, while being exposed to global culture and trends. Its influence on individual identity can influence the way young people understand themselves and interact with society. However, these impacts are not always positive, and the risk of negative impacts needs to be considered. Therefore, digital education and a balance between online and offline life are crucial in helping young people form a healthy and inclusive identity.